Quinone reactivity: Investigation of their contribution to nonenzymatic browning - Yiran Yu; Dandan Chen; Wei Li; Yao Mou; Yaqian Geng; Fang Chen; Xiaosong Hu; Junfu Ji; Lingjun Ma (Food Frontiers, 2023)
Abstract Browning is a severe problem in the juice industry, which is tremendously affected by quinone (Q) reactivity. Here, the formation rate, electrophilicity, and oxidizing ability of different quinones were investigated. LC/MS was applied to monitor the loss of polyphenols and quinones in model systems during storage. Mathematical modeling of collected LC/MS data was conducted to derive the rate constants of various reactions. Polyphenols containing catechol or pyrogallol groups are more susceptible to oxidation. Periodic acid and quinone mediated oxidation were faster than the autoxidation of polyphenols. Chlorogenic acid (CQA) and 4‐methylcatechol (4MC) only containing B ring can hardly contribute to browning. They must combine with A ring to form yellow polymers. Furthermore, the electrophilicity and oxidizing ability order of quinone is: CQA‐Q ≈ 4MC‐Q > catechin quinone (CAT‐Q) ≈ epicatechin quinone (EC‐Q) > gallic acid quinone (GA‐Q). It was possible that CAT‐Q and EC‐Q would undergo nucleophilic addition with their A rings and GA‐Q's extra hydroxyl group might contribute to the electrons, resulting in lower reactivity. This work innovatively evaluated the reactivity of diverse polyphenols and quinones, attempting to illustrate their contributions to nonenzymatic browning. These findings provide a new perspective to restrain the browning in the juice processing industry.